Da redemocratização do Brasil através das Constituições de 1946 e 1988 - Simon Riemann Costa e Silva (Araucaria)
This paper analyzes the process of re-democratization in Brazil through the Constitution of 1946 and the Constitution of 1988.Both constitutions represented a turning point from dictatorship to democracy to establish a democratic state. The study of the meaning of its limits and possibilities in each moment of history help to understand and work harder to build a real democracy in Brazil.